Synthesis of a Radiating Elements for Side Lobe Reduction Using a Hybrid Beamforming Technique Based on Non-Linear Programming and Stochastic Optimization - Brahimi, Mohamed; İnç, Mustafa; Ahmad, Hijaz; Menni, Younes; Lorenzini, Giulio (Int Information & Engineering Technology Assoc, 2022)
In this article, an algorithm with global constraints known as hybrid non-linear programming with particle swarm enhancement is available for improving the circular antenna array (CAA) radiation characteristics. The suggested method combines the optimization of excitation currents with the array's element spacing to create the correct beam patterns. In this context, adaptive particle optimization (APSO) and basic particle swarm optimization (BPSO) algorithms are applied with the previous method to the (8,12,20) elements to tune the array's amplitude and positioning to achieve a radiation profile with reduced SLL. The simulated results show that the recommended strategy provides the greatest decrease in side lobe levels and directivity.
Keywords: non-linear programming; stochastic optimization; mathematical modeling; circular antenna elements; side lobe level; particle swarm enhancement